Retrospective Cohort Study of Effectiveness and Safety of Adalimumab Use in Children with Juvenile Idiopathic Arthritis in the Republic of Bashkortostan - V. A. Maliyevskiy; O. A. Maliyevskiy; G. R. Gareyeva; L. S. Nazarova; A. A. Khasanova; A. Z. Nuriyakhmetova; D. D. Prolygina (Union of pediatricians of Russia, 2016)
Background: Methotrexate is the first-line drug for treating patients with juvenile idiopathic arthritis (JIA). If it is ineffective or intolerable, prescription of genetically engineered biopharmaceuticals is indicated. Objective: The study was aimed at assessing effectiveness and safety of genetically engineered biopharmaceutical adalimumab for treating children with JIA. Methods: A retrospective cohort study was conducted to analyze results of treating patients with JIA aged 2-17 years. Adalimumab would be prescribed biweekly in the dose of 24 mg/m2 (body surface) subcutaneously (if body weight is under 30 kg) or in the dose of 40 mg/m2 (if body weight is > 30 kg). Effectiveness and safety would be assessed after 4-12-24-48-96 weeks. Results: We analyzed treatment results of 17 patients (15 children with active joint syndrome, 2 - with active uveitis). All patients with active joint syndrome had been receiving adalimumab for 12 weeks, 12 patients - for 24 weeks, 8 - for 48 weeks, 5 - for 96 weeks. 30/50/70% improvement in terms of the ACRpedi criteria was observed in 15/11/4 children after 4 weeks, after 12 weeks - in 15/13/11 patients, after 48 weeks - in 7/6/6 patients. The status of inactive disease was established in 5 patients (33%) after 12 weeks, after 24 weeks - in 9 children (75%), after 48 weeks - in 7 children (70%), after 96 weeks - in 4 (80%) children. Active uveitis was terminated in all 5 patients with signs of eye damage in the treatment onset. 1 patient suffered from exacerbation of the disease after 48 weeks of therapy; the drug was withdrawn. Tubercular infection without local manifestations was established in 1 patient after 96 weeks (positive Mantoux test, papule - 10 mm). Adalimumab injection was terminated for the period of chemotherapy. Conclusion: Adalimumab has a sufficiently high effectiveness and safety for long-term (up to 2 years) treatment of children with JIA.